Pengaruh Pembelajaran Talking Stick Berbantuan Modul Interaktif Terhadap Hasil Belajar IPS Kelas V SDN 2 Payaman - Ritma Mutaqwa; Septiyati Purwandari (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
The purpose of this study was to determine the effect of talking stick learning assisted by interactive modules on social studies learning outcomes for fifth grade students at SD N 2 Payaman. The approach used in this study is quasi-experimental research, by conducting 5 treatments, namely being given treatment through learning using talking stick learning. The subjects of this study were 66 students who were divided into 2 groups, namely the experimental group and the control group. There are two variables used in the study, namely the dependent variable in the form of talking stick learning assisted by interactive modules, and the independent variable in the form of social studies learning outcomes of students. The data collection method is in the form of a test. The data analysis technique used is the independent sample t test. The data obtained were analyzed using the T test. The results showed that the talking stick learning aided by the interactive module had a positive effect on student social studies learning outcomes. Based on the results of the T posttest test for both groups conducted by the authors, tcount > ttable was 16.169 > 1.99773 and the average value of the experimental group was 81.6 with a percentage of 54%. These results indicate that the social studies learning outcomes of the experimental group students are higher than the control group.